Keeping up with the Joneses: Other-regarding Preferences and Endogenous Growth - Luke Petach; Daniele Tavani (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study a series of sustained growth models in which households' preferences are affected by the consumption of other households as summarized by average consumption. In endogenous growth models, the equilibrium paths involve lower savings and lower growth than the corresponding efficient paths. Both savings and growth are inversely related to the extent of social preferences. In semi-endogenous models, other-regarding preferences have no growth effects, but have positive level effects on the long-run research intensity, because they increase the market size for potential monopolists in the intermediate goods sector. To test the extent to which consumption is other-regarding, we use Consumer Expenditure Survey data: our identification strategy relies on a two-stage estimator that uses the Tax Reform Act of 1986 and the Omnibus Budget Reconciliation Act of 1993 as a positive and a negative consumption shocks to top incomes respectively. In the first stage, we use a difference-in-difference approach to exploit the exogenous variation in consumption caused by federal tax reform. We then use the predicted values for average within-cohort consumption by income deciles as an instrument to estimate the extent of social preferences. Our results point toward highly significant long-run `keeping up' effects on the order of 30%.
Keywords: D12; E21; O41; O51; 330; Keeping up with the Joneses; Endogenous Growth